Altruism, cooperation, and efficiency: Agricultural production in polygynous households - Richard Akresh; Joyce J. Chen; Charity Moore (Institute for the Study of Labor (IZA), 2011)
Altruism among family members can, in some cases, inhibit cooperation by increasing the utility that players expect to receive in a non-cooperative equilibrium. To test this, we examine agricultural productivity in polygynous households in West Africa. We find that cooperation is greater - production is more efficient - among co-wives than among husbands and wives because co-wives are less altruistic towards each other. The results are not driven by scale effects or self-selection into polygyny. Nor can they be explained by greater propensity for cooperation among women generally or by the household head acting as an enforcement mechanism for others' cooperative agreements.
urn:nbn:de:101:1-201203016476
Keywords: D13; D70; J12; O13; O55; 330; altruism; non-cooperative behavior; household bargaining; polygyny; Africa; Familienökonomik; Altruismus; Ehe; Verhandlungen; Nichtkooperatives Spiel; Westafrika